2021
DOI: 10.1055/s-0040-1722226
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs and Monocyte–Platelet Aggregate Formation in Acute Coronary Syndrome

Abstract: Background Monocyte–platelet aggregates (MPAs) are a sensitive marker of in vivo platelet activation in acute coronary syndrome (ACS) and associated with clinical outcomes. MicroRNAs (miRs) play an important role in the regulation of platelet activation, and may influence MPA formation. Both, miRs and MPA, could be influenced by the type of P2Y12 inhibitor. Aim To study the association of platelet-related miRs with MPA formation in ACS patients on dual antiplatelet therapy (DAPT), and to compare miRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…later compared the ratio of miR-126a between aspirin treatment patients and non-responders, and the results revealed that the level of miR-126a decreased after aspirin treatment ( 124 ). Furthermore, cessation of miRNAs, including miRNA-223, miRNA-21, miRNA-150, and miRNA-126, are associated with the regulation of the P2Y12 receptor and thus affect platelet aggregation ( 125 127 ). Zhang et al.…”
Section: The Role Of Mirna In the Clinical Application Of Kawasaki Di...mentioning
confidence: 99%
“…later compared the ratio of miR-126a between aspirin treatment patients and non-responders, and the results revealed that the level of miR-126a decreased after aspirin treatment ( 124 ). Furthermore, cessation of miRNAs, including miRNA-223, miRNA-21, miRNA-150, and miRNA-126, are associated with the regulation of the P2Y12 receptor and thus affect platelet aggregation ( 125 127 ). Zhang et al.…”
Section: The Role Of Mirna In the Clinical Application Of Kawasaki Di...mentioning
confidence: 99%
“…The study from Stojkovic et al assessing the relationship between different circulating miRNAs and monocyte-platelet aggregate formation in patients with acute coronary syndrome on dual antiplatelet therapy is an example of such new interest. 96 Garcia et al identified an important role of a specific miRNA, miR-204-5p, on in vitro platelet production and function, 97 suggesting genetic control of platelet production and function by miR-204-5p which may thus be considered as a new biomarker for high platelet reactivity in the context of personalized antiplatelet therapy. 98 The comprehensive overview of currently available techniques for studying miRNA function with a focus on platelet reactivity regulation by Garcia et al, 99 also attracted much interest among our author community seeking to overcome the current methodological limitations in this field.…”
Section: Identifying New Targets and Mechanismsmentioning
confidence: 99%
“…We aimed to determine the prognostic performance of selected circulating miRNAs for all-cause mortality and their potential usefulness as biomarkers in T2DM patients on antiplatelet treatment. Several studies showed the role of miR-126 and miR-223 in the context of antiplatelet treatment in many different cohorts [ 16 , 19 , 20 , 21 , 22 , 23 ]. Changes in plasma miRNAs in response to antiplatelet therapy were investigated in a small cohort of healthy volunteers [ 16 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al analyzed the correlation between plasma miR-126 and miR-223, among others, and the risk of major adverse cardiovascular events in patients on dual antiplatelet therapy (DAPT) after percutaneous coronary intervention [ 16 , 19 , 20 , 21 , 22 , 23 ]. The association between miRNAs and platelet reactivity was also studied in patients with acute coronary syndrome (ACS) on various antiplatelet therapies [ 16 , 19 , 20 , 21 , 22 , 23 ]. In a similar study Carino et al assessed miR-126 and miR-223, among other miRNAs, in patients with ACS before and after the therapeutic switch from DAPT to ticagrelor [ 16 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation